Redefining cutaneous lupus erythematosus: a proposed international consensus approach and results of a preliminary questionnaire. Issue 1 (26th March 2015) - Merola, J F; Nyberg, F; Furukawa, F; Goodfield, M J; Hasegawa, M; Marinovic, B; Szepietowski, J; Dutz, J; Werth, V P
Abstract : There is currently no uniform definition of cutaneous lupus erythematosus (CLE) upon which to base a study population for observational and interventional trials. A preliminary questionnaire was derived from and sent to a panel of CLE experts which demonstrated consensus agreement that (1) there is a need for new definitions for CLE (2) CLE is distinct from systemic lupus erythematosus and that a CLE grouping scheme should remain apart from current systemic lupus erythematosus schema (3) current CLE grouping schemes are inadequate around communication, prognostic information and to meet the needs of researchers, clinicians, patients and payers.